Forty-five years of puma research in Chile: trends, knowledge gaps, and conservation implications - Leichtle , Jorge; Larraguibel-González, Cristián (THERYA, 2026)
Research on the puma (Puma concolor) in Chile has progressively developed over the past 45 years; however, no comprehensive synthesis had previously evaluated its spatial, thematic, and temporal development. We conducted a systematic review of peer-reviewed studies published between 1980 and 2025, identifying 34 articles addressing ecological, behavioral, genetic, sanitary, and socio-environmental aspects of the species. Research effort was spatially uneven across the country. Although central Chile currently accounts for the largest proportion of studies, early research was historically concentrated in the Magallanes Region, while northern ecosystems remain comparatively underrepresented. Trophic ecology dominated the initial decades of research, whereas studies on behavior, distribution and density, health, genetics, and human–puma interactions increased markedly after 2010. Temporal analyses and Correspondence Analysis revealed clear shifts in research priorities, with the most recent period (2016–2025) characterized by greater thematic diversification and the incorporation of molecular and socio-ecological approaches. Despite these advances, important gaps persist, particularly in long-term monitoring, telemetry-based studies, disease ecology, and research in arid or highly fragmented landscapes. Socio-ecological research remains limited relative to the growing challenges of human–puma coexistence in human-dominated environments. By providing the first integrated assessment of four and a half decades of puma research in Chile, this review establishes a baseline to guide future interdisciplinary and geographically representative conservation efforts.